Quality of Life Analysis of HPV-Positive Oropharyngeal Cancer Patients in a Randomized Trial of Reduced-Dose Versus Standard Chemoradiotherapy: 5-Year Follow-Up - Takahashi, Mai; Hwang, Michael; Misiukiewicz, Krysztof; Gupta, Vishal; Miles, Brett A.; Bakst, Richard; Genden, Eric; Selkridge, Isaiah; Botzler, John; Virani, Vruti; Moshier, Erin; Bonomi, Marcelo R.; et al. (Frontiers in Oncology, 2022)
Background: Human Papillomavirus-positive oropharyngeal carcinoma (HPVOPC) portends a more favorable prognosis compared to environmentally-related oropharynx cancer (EROPC). Patients with HPVOPC may be overtreated and endure unnecessary long-term toxicities. Methods: Patients with untreated, locally-advanced HPVOPC received induction chemotherapy with docetaxel, cisplatin, and 5-fluorouracil and were randomized to sdCRT (70 Gy) or rdCRT (56 Gy) with weekly carboplatin. Patients were followed for 5-year progression-free survival (PFS), overall survival (OS), and changes in five validated quality of life (QoL) surveys. Results: Twenty patients were enrolled and randomized to rdCRT (n=12) or sdCRT (n=8). Median follow-up was 88 months. 5-year PFS/OS were 87.5%/83.3% for sdCRT and rdCRT respectively. At 5 years follow up, difference in QoL changes all favored the rdCRT arm and two QoL scales reached statistical significance. Conclusions: rdCRT after TPF in HPVOPC is feasible. These limited results demonstrate equivalent long-term survival compared to sdCRT and are more favorable in specific QoL domains.